Effects of Environmental Variation in Structuring Population Genetic Variation in the False-Water Cobras (Xenodontinae: Hydrodynastes) - Carvalho, Priscila S. [UNESP]; Santana, Diego J.; Zaher, Hussam; Myers, Edward A. (Springer Nature, 2023)
Although rivers are known to promote diversification and shape phylogeographic patterns, they can also be permeable and facilitate the dispersal of species. Using multiple molecular methodological approaches, we conducted a phylogeographic investigation of two semiaquatic snake species with continental distributions across South America, testing how environmental and historical factors (e.g., potential allopatric divergence across rivers) have affected their evolutionary history. Our results show that Hydrodynastes gigas and H. bicinctus have a recent divergence time (~1.5 mya) and that both species have low genetic diversity with no geographic structure. Population genetic divergence in H. gigas is explained by geographic distance (isolation-by-distance), climate (isolation-by-environment), and hydrographic basin. Paleo-niche models suggest that historically stable regions of habitat suitability for both taxa are largely restricted to the La Plata basin. We suggest that life history traits of these species, for example high dispersal capabilities and generalist ecologies, have allowed for their extensive geographic distributions and population connectivity resulting in no geographic structure and low genetic variation.
Keywords: Climatic changes; Dipsadidae; Evolution; Niche modeling; Phylogeography; Squamata; Watershed